DISTURBIO OBSESSIVO-COMPULSIVO E QUADROS CORRELATOS NA CLINICA DERMATOLOGICA - Torres, Albina Rodrigues [UNESP]; Inaty Smaira, S. [UNESP]; Tiosso, A. M. [UNESP] (My University, 1995)
The article describes the obsessive-compulsive disorder (OCD), a not uncommon mental illness, of an unknown origin, for the most part, which can cause important dermatoses. Some OCD-related disorders of importance in dermatologic practice are also described, such as: body dysmorphic disorder, trichotillomania, onychophagia and factitial dermatitis. The importance of the proper identification of these disorders is stressed for the application for adequate therapy.
Obsessive-compulsive disorders and clinically correlated dermatoses
Keywords: obsessive-compulsive disorders; skin disease; human; obsession; psychotherapy; short survey